Polyaniline modified magnetic nanoparticles coated with dicationic ionic liquid for effective removal of rhodamine B (RB) from aqueous solution - Shahriman, Mohamad Shariff; Mohamad Zain, Nur Nadhirah; Mohamad, Sharifah; Abdul Manan, Ninie Suhana; Mohd Yaman, Suhaila; Asman, Saliza; Muggundha, Raoov (The Royal Society of Chemistry, 2018)
Polyaniline (PANI) modified magnetic nanoparticle (MNP) nanocomposites coated with newly synthesized dicationic ionic liquid (DICAT) forming MNP-PANI-DICAT were successfully synthesized as a potential material for the removal of Rhodamine B (RB) from water samples. The synthesized material was successfully characterized using a few techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray powder diffraction (XRD), thermo gravimetric analysis (TGA), Brunauer–Emmett–Teller (BET), and transmission electron microscopy (TEM) analysis. Several parameters have been optimized to enhance the efficiency of the removal process. The adsorption kinetics were investigated and the results showed that MNP-PANI-DICAT was best fitted to a pseudo-second order model for the adsorption of RB. As for the isotherm studies, Temkin's model was found to fit well with the adsorption isotherm of RB on MNP-PANI-DICAT. Other than that, thermodynamics results showed negative values of DG for the adsorption of RB, which indicated that the process is thermodynamically feasible, spontaneous and chemically controlled at lower temperature. The negative value of enthalpy DH (40.41) indicated that the adsorption was an exothermic process. The percentage removal of RB was found to be 94.7% by MNP-PANI-DICAT under optimized conditions.